Assessing policy preferences amongst climate change adaptation and disaster risk reduction stakeholders using serious gaming. (December 2020) - Abad, Jaime; Booth, Laura; Baills, Audrey; Fleming, Kevin; Leone, Mattia; Schueller, Lynn; Petrovic, Bojana
Abstract: The ESPREssO Project set out to propose ways to inform more coherent national and European approaches on Disaster Risk Reduction (DRR) and Climate Change Adaptation (CCA). A critical step in this process is the identification of existing barriers to effective collaboration, finding new areas of common ground, and ways to enhance co-operation with regards to CCA and DRR policymaking in Europe. This is particularly important considering the potential relationships between CCA and DRR activities at the regional, national, European and global levels. Serious games have emerged as a valuable tool to communicate information and catalyse discussion in many policy arenas. The games have the power to inform, mainly by exposing strengths and weaknesses of a system but not necessarily create policy choices. This paper presents the development process and rationale behind creation of RAMSETE I, a serious game developed by and for the ESPREssO Project to elicit information from its stakeholders in aiming to inform synergies between CCA and DRR sectors. The results assess its application as a device to frame discussions during an international Think Tank workshop. The serious game focused on three particular aspects of CCA and DRR policy interactions: (1) separation of administrative responsibilities and the use of different terminology, (2) the ongoing competition for funding and political will as well as (3) difficulties regarding the top-down implementation of policies. The rules and design process are presented briefly, before going in-depth into the information gleaned during its application in the workshop.